Estratégias operacionais para o envio de lodo aeróbio para adensamento e estabilização em reatores UASB : estudo de caso de uma estação em escala plena - Saulo Nonato de Souza (2020)
The present work sought to evaluate, in a full-scale WWTP made up of a UASB reactor, post-treatment by trickling filters (TF) and dehydration system with drying beds, the effect of different strategies for sending aerobic sludge generated in the TF to densification and digestion in UASB reactors. The hydraulic and performance impacts on the UASB reactors, as well as on the station as a whole, were evaluated. To this end, 4 phases were defined for the study, in which different protocols for sending aerobic sludge to the UASB reactor were tested. The COD and TSS parameters were monitored in the affluent (raw sewage + excess aerobic sludge + septic tank sludge), in the effluent from the UASB reactor and in the final effluent from the WWTP. During 3 phases, the protocol for sending excess aerobic sludge was carried out continuously (Phase DC1 - Qlodo = 1.5 L / s and HDTUASB = 6.1 h; Phase DC2 Qlodo = 1.0 L / s and HDTUASB = 12.7 h; Phase DC3 - Qlodo = 1.0 L / s and HDTUASB = 7.8 h), while in phase 4 the sending of excess aerobic sludge was performed only at night, at the time of 0h to 01h (Phase DN - Qlodo = 6.6 L / s and HDTUASB = 7.8 h). The regime of receiving sludge from septic tank, added to the affluent flows of raw sewage and excess aerobic sludge, implied an apparent hydraulic overload in the UASB reactors during phases DC1, DC3 and DN, in which only one UASB reactor was in operation . The checks carried out showed that in these three phases the hydraulic parameters HDT, Vup and and HDTcd were with median values above or below the limits recommended in the standard (NBR 12.209 / 2011), mainly between 11 am and 11 pm. The different strategies tested for sending excess aerobic sludge did not impact the hydraulic parameters of the post-treatment unit (TF). The UASB reactors showed COD removal efficiencies that ranged from 53% in the DC1 phase, to 61% in the DC2 phase, while the TSS removal efficiencies ranged from 61% in the DC2 phase to 73% in the DC3 phase. It is noteworthy that there was no significant difference between the observed values. The median concentrations of TSS in the treated effluent of the UASB reactors did not show significant difference and varied from 70 mg/L in the DC3 phase to 89 mg/L in the DC2 phase. The median COD values in the treated effluent from the UASB reactors did not show any significant difference between the DC1, DC2 and DN phases, with a variation from 208 mg/L in the DC1 phase to 231 mg/L in the DN phase. Apparently the protocols for the disposal of excess sludge tested, continuously and intermittently, did not imply significantly different concentrations (α = 0.05) for the COD parameter in the effluent of the WWTP. In 100% of the results, the WWTP met the release standard provided for in the environmental legislation for the efficiency of COD removal and for the concentrations of COD and TSS in the final effluent of the station. The COD concentration in the effluent from the WWTP ranged from 63 mg/L in the DC2 phase to 88 mg/L in the DC3 phase. While the median TSS values at the outlet of the secondary sedimentation unit ranged from 20 to 29 mg/L. The management of the excess anaerobic sludge was carried out with ST concentrations ranging from 1.0 to 1.5%, which caused an overload of sludge in the drying beds of the WWTP, due to the high volumes of sludge discarded per cycle. In general, no overhead was observed in the rate of application of solids in the beds. The excess aerobic sludge, sent for densification and digestion in the UASB reactors, presented values of median ST concentrations that varied from 0.04% in the DC2 phase to 0.45% in the DN phase. The general results of the research indicated that the protocols for sending excess aerobic sludge, for densification and digestion in the UASB reactors, did not compromise the overall performance of the station and of the UASB reactors when evaluated separately, indicating that they can be adopted as an operational strategy at WWTP Mateus Leme or tested at other stations at full scale.